Gastric tonometry versus cardiac index as resuscitation goals in septic shock: A multicenter, randomized, controlled trial - Palizas, Fernando (2009)
Introduction: Resuscitation goals for septic shock remain controversial. Despite the normalization of systemic hemodynamic variables, tissue hypoperfusion can still persist. Indeed, lactate or oxygen venous saturation may be difficult to interpret. Our hypothesis was that a gastric intramucosal pH-guided resuscitation protocol might improve the outcome of septic shock compared with a standard approach aimed at normalizing systemic parameters such as cardiac index (CI). Methods: The 130 septic-shock patients were randomized to two different resuscitation goals: CI ≥ 3.0 L/min/m2 (CI group: 66 patients) or intramucosal pH (pHi) ≥ 7.32 (pHi group: 64 patients). After correcting basic physiologic parameters, additional resuscitation consisting of more fluids and dobutamine was started if specific goals for each group had not been reached. Several clinical data were registered at baseline and during evolution. Hemodynamic data and pHi values were registered every 6 hours during the protocol. Primary end point was 28 days' mortality. Results: Both groups were comparable at baseline. The most frequent sources of infection were abdominal sepsis and pneumonia. Twenty-eight day mortality (30.3 vs. 28.1%), peak Therapeutic Intervention Scoring System scores (32.6 ± 6.5 vs. 33.2 ± 4.7) and ICU length of stay (12.6 ± 8.2 vs. 16 ± 12.4 days) were comparable. A higher proportion of patients exhibited values below the specific target at baseline in the pHi group compared with the CI group (50% vs. 10.9%; P < 0.001). Of 32 patients with a pHi < 7.32 at baseline, only 7 (22%) normalized this parameter after resuscitation. Areas under the receiver operator characteristic curves to predict mortality at baseline, and at 24 and 48 hours were 0.55, 0.61, and 0.47, and 0.70, 0.90, and 0.75, for CI and pHi, respectively. Conclusions: Our study failed to demonstrate any survival benefit of using pHi compared with CI as resuscitation goal in septic-shock patients. Nevertheless, a normalization of pHi within 24 hours of resuscitation is a strong signal of therapeutic success, and in contrast, a persistent low pHi despite treatment is associated with a very bad prognosis in septic-shock patients.